2013
DOI: 10.1038/onc.2013.368
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc and Her2 cooperate to drive a stem-like phenotype with poor prognosis in breast cancer

Abstract: The HER2 (ERBB2) and MYC genes are commonly amplified in breast cancer, yet little is known about their molecular and clinical interaction. Using a novel chimeric mammary transgenic approach and in vitro models, we demonstrate markedly increased self-renewal and tumour-propagating capability of cells transformed with Her2 and c-Myc. Coexpression of both oncoproteins in cultured cells led to the activation of a c-Myc transcriptional signature and acquisition of a self-renewing phenotype independent of an epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 80 publications
8
77
2
Order By: Relevance
“…Instead, new data have shown that this coamplification is associated with poor outcome and is associated with the sequence of acquisition of a malignant stem cell-like phenotype that maintains lower growth and therefore may be a key target of new therapy. 28 TOP2A resides very close to ERBB2 on the chromosome and its amplification was only observed with the concomitant amplification of ERBB2. However, TOP2A is not simply a 'passenger' gene because TOP2A encodes an enzyme, topoisomerase IIα, which is required for DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, new data have shown that this coamplification is associated with poor outcome and is associated with the sequence of acquisition of a malignant stem cell-like phenotype that maintains lower growth and therefore may be a key target of new therapy. 28 TOP2A resides very close to ERBB2 on the chromosome and its amplification was only observed with the concomitant amplification of ERBB2. However, TOP2A is not simply a 'passenger' gene because TOP2A encodes an enzyme, topoisomerase IIα, which is required for DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…39 Positive TLR3 expression was considered a favorable prognostic factor whereas positive c-Myc protein expression is a poor prognostic factor by clinical research of NB. 8,20 However, elevated TLR3 expression in breast cancer and overexpression of c-Myc in HER2-positive breast cancer were respectively determined as a poor prognostic factor, 40,41 and TLR3 treatment was associated with overexpression of c-Myc to facilitate stem cells potential. 40 In addition, overexpression of TLR3 and c-Myc was reported to be induced by poly(I:C) treatment, which led to cell proliferation in head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Combination treatment with triptolide and hydroxycamptothecin synergistically enhances apoptosis by increasing the ratio of Bax/Bcl-2 in A549 cells (24). Formononetin-induced apoptosis was accompanied by upregulation of Bax and downregulation of Bcl-2, with the consequent dysfunction of mitochondria and activation of caspase-3 in A549 cells (25). Cactus pear extracts increased caspase3 and Bax protein levels, and decreased the Bcl-2 protein level in the lung cancer cell line A549 (26).…”
Section: Discussionmentioning
confidence: 97%